Simplified Method for Shear Strength Prediction of Confined Masonry Walls Subjected to in Plane Loads. (2016) - Sreejith, P.P.; Sivan, P.P.; Praveen, A.; Gajendran, C.; Nisha, V.
Abstract: The paper deals with the shear strength prediction of confined masonry wall subject to in-plane horizontal loading and to investigate the possibility of using strut and tie model for predicting the ultimate strength of confined masonry walls subjected to in plane loads. Shear strength of confined masonry wall subject to in plane horizontal loading are calculated using strut and tie analysis, MSJC-2013 recommendations, EC6 recommendations, and finite element analysis. The result obtained is compared to check the accuracy of the different methods used.